Pembinaan Karakter Religius Siswa Melalui Program Bina Pribadi Islami di SMA IT Fitrah Insani Kabupaten Bandung Barat - Nurul Azizah Chaniago (UNISBA Press, 2024)
Abstract. Religious character development in schools plays a crucial role in education, especially in Islamic schools. This research explores the Islamic Personal Development Program at SMA IT Fitrah Insani in West Bandung Regency, focusing on planning, organization, implementation, and evaluation. The research method used is qualitative descriptive with data collection techniques including case studies, interviews, and observations. The results reveal that the planning of this program involves strong collaboration among various stakeholders, encompassing curriculum development, materials, modules, and implementation strategies. The organization of the program includes a comprehensive organizational structure, with active monitoring by mentor teachers and involvement of parents in the evaluation. To ensure program effectiveness, there is a need to enhance the organizational system and coordination among stakeholders. The program implementation involves students leading various activities to train their leadership skills. Although the program is effective in shaping the religious character of students, there is a recommendation to diversify teaching methods and initiate the program in the morning. Regular evaluations of the program are conducted by various parties, including the school principal, mentor teachers, class guardians, and parents. The evaluations indicate parental satisfaction with the program, although suggestions for improvement are provided. This research supports previous findings that involving various parties in program evaluation provides a more holistic understanding of its effectiveness. In conclusion, the Islamic Personal Development Program at SMA IT Fitrah Insani has been successful in cultivating the religious character of students, although there is room for improvement at each stage. Abstrak. Pembinaan karakter religius di SMA IT Fitrah Insani Kabupaten Bandung Barat memiliki peranan vital dalam pendidikan, khususnya di lingkungan Islam. Penelitian ini mengeksplorasi Program Bina Pribadi Islami di SMA IT Fitrah Insani Kabupaten Bandung Barat dengan fokus pada aspek perencanaan, pengorganisasian, pelaksanaan, dan evaluasi. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan menggunakan studi kasus, wawancara, dan observasi sebagai teknik pengumpulan data. Hasil penelitian menunjukkan bahwa perencanaan program ini melibatkan kerjasama yang erat antara berbagai pihak, melibatkan pengembangan kurikulum, materi, modul, dan strategi pelaksanaan. Pengorganisasian program mencakup struktur organisasi yang komprehensif, dengan pengawasan aktif oleh guru pembina dan keterlibatan orang tua dalam evaluasi. Untuk memastikan efektivitas program, perlu ditingkatkan sistem pengorganisasian dan koordinasi di antara stakeholder. Pelaksanaan program melibatkan siswa dalam memimpin berbagai kegiatan untuk melatih kemampuan kepemimpinan mereka. Meskipun program ini terbukti efektif dalam membentuk karakter religius siswa, ada saran untuk memvariasikan metode pengajaran dan memulai program di pagi hari. Evaluasi program secara berkala dilakukan oleh berbagai pihak, termasuk kepala sekolah, guru pembina, wali kelas, dan orang tua. Evaluasi ini menunjukkan kepuasan orang tua terhadap program, meskipun memberikan saran untuk perbaikan. Penelitian ini mendukung temuan sebelumnya bahwa melibatkan berbagai pihak dalam evaluasi program memberikan pemahaman yang lebih komprehensif tentang efektivitasnya. Kesimpulannya, Program Bina Pribadi Islami di SMA IT Fitrah Insani telah berhasil dalam membina karakter religius siswa, meskipun masih terdapat ruang untuk peningkatan di setiap tahap.